Inclusive Practices: Levels of Teacher Collaboration in Regular Schools - Widodo, Agus Pratomo Andi; Hufad, Achmad; Sunardi, Sunardi; Hardi, Enny; Safitri, Adinda (Journal of ICSAR, 2023)
This research aims to analyze the collaborative learning in inclusive schools from the perspective of teachers and its implementation. Collaborative learning will be a challenge if there are children with special needs and regular students learning together in inclusive class. This research used quantitative research method with descriptive approach. This research was conducted in 10 inclusive schools involving 20 teachers (10 special teachers and 10 regular teachers). The results showed the acceptance of the existence of children with special needs by regular teachers related to the collaboration process in inclusive schools. The collaboration levels that occurred were 50% very good (level 1), 30% good (level 2) and 20% poor (level 3). Collaborative learning will succeed when the regular teachers accept the existence of children with special needs.